2008
DOI: 10.1016/j.clay.2007.11.001
|View full text |Cite
|
Sign up to set email alerts
|

A study on the thermal conductivity of compacted bentonites

Abstract: Thermal conductivity of compacted bentonite is one of the most important properties in the design of high-level radioactive waste repositories where this material is proposed for use as a buffer. In the work described here, a thermal probe based on the hot wire method was used to measure the thermal conductivity of compacted bentonite specimens. The experimental results were analyzed to observe the effects of various factors (i.e. dry density, water content, hysteresis, degree of saturation and volumetric frac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
104
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(109 citation statements)
references
References 12 publications
5
104
0
Order By: Relevance
“…This equation is inspired in the formulation of De Vries's (1963) which according to Tang et al (2008) provides the best fit to measured thermal conductivity data for several bentonites, including the FEBEX bentonite. The formulation in Eq.…”
Section: Energy Balancementioning
confidence: 99%
“…This equation is inspired in the formulation of De Vries's (1963) which according to Tang et al (2008) provides the best fit to measured thermal conductivity data for several bentonites, including the FEBEX bentonite. The formulation in Eq.…”
Section: Energy Balancementioning
confidence: 99%
“…Several experimental studies have examined the thermal behavior of geo-materials over different conditions including material composition, dry density, saturation, and temperature (Coulon et al 1987;Beziat et al 1988;Radhakrisha et al 1989;Suzuki et al 1992;Borgensson et al 1994;Graham et al 1997;Madsen 1998;Villar 2002;Ould-Lahoucine et al 2002;Engelhardt and Finsterle 2003;Tang et al 2008;Ye et al 2010;Man et al 2011;Kim et al 2012;Likos 2014;Lee et al 2016). Baumgartner et al (2006) estimated the thermal conductivity and specific heat capacity of bentonite materials based on their composition and density.…”
Section: R a F Tmentioning
confidence: 99%
“…Barry-Macaulay et al (2015) also suggested that existing models may be improved upon using soil-specific calibration of the model inputs. Tang et al (2008) examined bentonite thermal data and found that thermal conductivity varied linearly with the volume fraction of air. Ideally thermal models for numerical models for deep geologic repositories would have an experimental basis, which is used to calibrate thermal conductivity constitutive models.…”
Section: R a F Tmentioning
confidence: 99%
See 1 more Smart Citation
“…These bentonites contain mainly montmorillonite, which is an essential mineral to ensure sealing properties. Beside the montmorillonite, there is quartz, which is also an important mineral for its particular in‰uence on thermal conductivity (Tang et al, 2008b). Note that a high thermal conductivity of the engineered barrier allows the heat to dissipate quickly from the canisters, consequently reducing the maximum temperature in the EBS.…”
Section: Introductionmentioning
confidence: 99%